Mediational role of risk perception in the relationship between vaccination knowledge and intention - Mohd Nazori, Mohd Nazir; Ismail, Rohani; Rasudin, Nur Syahmina; Mohamed, Rosminah; Mohd Noor, Norhayati; Sulli, Zailiza; Ahmad Zainuri, Noor Azliah; Jayapalan, Ashvini (Elsevier B.V., 2024)
Background: Previous studies have shown that parents demand for information on vaccinations is universal. Nonetheless, parental knowledge demonstrated mixed results in vaccination intention, attitude, uptake, or confidence. In contrast, risk perception is a consistent predictor of vaccination-related outcomes. Objective: This study aimed to establish risk perception as a mediator between vaccination knowledge and intention. Method: Using a multistage random sampling technique, a cross-sectional survey was conducted with expectant mothers from maternity and child health clinics in the districts of Petaling, Klang, Gombak, and Hulu Langat. 416 respondents answered the self-administered questionnaire. Data was analysed using SPSS version 27 for descriptive statistics and Amos version 27 with bootstrapping procedure for mediation analysis. Results: Vaccination knowledge predicted risk perception [std β = 0.743, p = 0.036], risk perception predicted vaccination intention [std β = 0.934, p = 0.006], and risk perception fully mediate the relationship between vaccination knowledge and intention [std β = 0.694, p = 0.016]. The mediation model showed satisfactory fit indices: χ2/df (2.898), comparative fit index 0.946, Tucker-Lewis index 0.939, and root mean squared error of approximation 0.061. Conclusion: The goal of educational interventions is to increase vaccination intention by addressing vaccine information that influences both subjective and objective risk perception.